Experimental analysis on internal combustion engine using MWCNT/water nanofluid as a coolant. (2020) - Muruganandam, M.; Mukesh Kumar, P.C.
Abstract: The present industries face the difficulties in satisfying out the cooling need as the conventional coolants have achieved their limitations. In this experimental investigation, the nanofluids have been prepared by using two-step methods at the volume concentrations of 0.1, 0.3 and 0.5% with addition of sodium do-decyl butane sulfonate (SDBS) as stabilizing agent observed that 0.3% nanofluids shows good stability even after 45 days of preparation. It is found that the mechanical efficiency and total fuel consumption of 0.3% nanofluids are 8 to 18% and 9 to18% respectively higher than water as coolant in the load ranges under consideration.